2015
DOI: 10.1371/journal.pone.0134682
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of TGFβR2 Is Associated with the Clinical Outcome of Non-Small Cell Lung Cancer Patients Treated with Chemotherapy

Abstract: To investigate the prognostic significance of TGFβR2 expression and chemotherapy in Chinese non-small cell lung cancer (NSCLC) patients, TGFβR2 expression NSCLC was analyzed in silico using the Oncomine database, and subsequently analyzed with quantitative RT-PCR in 308 NSCLC biopsies, 42 of which were paired with adjacent non-neoplastic tissues. Our results show that TGFβR2 expression was also increased in NSCLC biopsies relative to normal tissue samples and correlated with poor prognosis. TGFβR2 expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…However, the other research showed that TGFbR2 acted as a proto-oncogene; its expression was dramatically increased in non-small-cell lung cancer tissues compared with non-neoplastic tissues, and overexpression of TGFbR2 was a significant risk factor for decreased overall survival and disease-free survival in non-small-cell lung cancer patients. 30 The inconsistent expression of miR-155 and TGFbR2 might be explained by the differences in tumor classification, tumor staging, or immune functions. We should further address the biological functions of miR-155 and TGFbR2 in GC in future studies.…”
Section: In Vivo Role Of Mir-155 and Tgfbr2 In Gastric Cancermentioning
confidence: 99%
“…However, the other research showed that TGFbR2 acted as a proto-oncogene; its expression was dramatically increased in non-small-cell lung cancer tissues compared with non-neoplastic tissues, and overexpression of TGFbR2 was a significant risk factor for decreased overall survival and disease-free survival in non-small-cell lung cancer patients. 30 The inconsistent expression of miR-155 and TGFbR2 might be explained by the differences in tumor classification, tumor staging, or immune functions. We should further address the biological functions of miR-155 and TGFbR2 in GC in future studies.…”
Section: In Vivo Role Of Mir-155 and Tgfbr2 In Gastric Cancermentioning
confidence: 99%
“…Low levels of TGFβR2 proteins were negatively correlated with poor survival in patients with nasopharyngeal carcinoma [13]. However, some researchers found that TGFβR2 as a proto-oncogene, the expression was significantly higher in NSCLC tissues than in non-neoplastic tissues, and high expression of TGFβR2 was a critical risk factor for reduced survival in NSCLC patients [7]. And in subsequently vitro experiments, TGFβR2 could promote malignant characteristics in A549 [28] and H1299 cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…The blockade of TGFβ signaling is always through either interrupt of TGFβ responses or the development of genetic alterations and epigenetic modifications in its components especially TGFβR2 [11]. As a tumor-suppressor gene, TGFβR2 is down-regulated in multiple cancer types [7, 1214]. Then cancer cells lose their sensitivity to TGFβ-mediated growth inhibitory effect due to TGFβR2 down-regulation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Triller et al (67) observed a significant negative correlation between MRP1 expression and a more favorable response rate to chemotherapy in patients with NSCLC. Similarly, it is worth noting that increased expression of ABCG4 and transforming growth factor β receptor type 2 are also identified as novel poor prognostic factors of chemotherapy in NSCLC patients (68,69). It is possible that an increase in MRP1-mediated efflux of anti-neoplastic agents reduces the intracellular concentration, and thereby decreases the therapeutic efficacy of the agents.…”
Section: Discussionmentioning
confidence: 99%